Determinants of Stunting in Toddlers: An Analysis of Social, Economic, and Child-Rearing Factors in the Community - Muti Atun Nafi’ah (PT. AVID MEDIA INDONESIA, 2026)
Stunting among toddlers remains a critical public health issue due to its long-term impact on cognitive development, productivity, and socio-economic outcomes. This study aims to analyze the determinants of stunting incidence by focusing on social, economic, and parenting factors within the community context. A qualitative approach with a descriptive-exploratory design was employed. Data were collected through in-depth interviews, focus group discussions, observations, and document analysis involving mothers, health workers, and community representatives selected using purposive sampling. The data were analyzed using thematic analysis to identify key patterns and relationships among variables. The findings reveal that stunting is influenced by interconnected factors across multiple dimensions. Social factors such as cultural norms and limited family support affect caregiving practices, while economic constraints—particularly low income and food insecurity restrict access to adequate nutrition and healthcare services. Parenting practices, including breastfeeding, complementary feeding, and child care during illness, emerge as the most critical determinants, acting as a pathway through which social and economic conditions influence child growth. Environmental conditions and limited utilization of health services further exacerbate the risk of stunting. In conclusion, stunting is a multidimensional problem requiring integrated interventions that address socio-economic inequalities, strengthen parenting practices, and improve access to health services to achieve sustainable reductions in prevalence